Pengembangan Aplikasi Parkir Berbasis Web Menggunakan Metode RFID Untuk Manajemen Parkir (Studi Kasus: PT. Prama Jaya Arja) - Purniawan, Adi; Nanang (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
In the current digital era, the parking system is experiencing a significant transformation with the application of advanced technology to increase efficiency and user comfort. This research aims to develop a web-based parking application with Radio Frequency Identification (RFID) technology implemented at PT. Prama Jaya Arja, to minimize queues, reduce the potential for human error, and increase security in the parking area. This application was developed using the PHP, MySQL and JavaScript programming languages ​​for the database, which allows integration with RFID technology and supports a more efficient parking management system. The methodology used is the Waterfall method, which includes the stages of needs analysis, design, implementation, testing and maintenance. The research results show that this web-based parking application has succeeded in parking management efficiency by minimizing queues and the potential for human error, as well increasing speed and accuracy in the parking management process. This system facilitates convenience for PT users and managers. Prama Jaya Arja through non-cash payment features, real-time parking reporting, as well as automatic monitoring of vehicles entering and leaving the parking area.